Towards a rigorous fusion of GNSS and InSAR observations for the purpose of water vapor retrieval - Heublein, MarionAlshawaf, FadwaMayer, MichaelHinz, StefanHeck, Bernhard (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2014)
In the framework of the rigorous fusion of GNSS and InSAR observations, the presented work carries out at a straightforward comparison of the wet delay, caused by water vapor, derived from GNSS and InSAR. The contributions of the two sensors to the wet delay are compared in the line of sight towards the SAR satellite. Comparisons of GNSS observations with the satellite-directed InSAR data show that only a partial component of the wet delay remains after the interferogram formation.